STRATEGI PENGEMBANGAN AGRIBISNIS KARET RAKYAT DI KABUPATEN NIAS SELATAN - Ujianhati Zega; Buhari Sibuea (JURNAL AGRICA, 2018)
The form of this research is descriptive quantitative research with observational methods (survey) and field observations. The analysis used the descriptive analysis of the literature study for quantitative analysis of secondary data and primary data collected for the research instrument in the form of a list of questions. Research sample were 105 respondents from 95 districts sampled farmers and 10 key figures in the study area. The results of this study are: The results of the analysis of internal strategic factors consist of 1) the power factor: land availability, high employment, good soil fertility to the rubber, the availability of human and socio-cultural factors. 2) Factors weakness :, no rubber factories, rubber prices are still low, there is no rejuvenation program, farmers and low capital. External strategic factors in South Nias consists of 1) Factor odds: high export demand, the expansion of the land is still available, the strong commitment of the local government, land use and does not require any displaced high-tech. 2) Factors :, threats land conversion, farmers shift to other sectors, climate change, pests and diseases and premature felling of rubber trees productive. Offered an alternative strategy for the development of rubber in South Nias are: 1) Establish farmer groups as a means of counseling, education, the introduction of technology and access permodalan.2) Capital to petani.3) rejuvenation program to clone old unggul.4) Utilize budget autonomy to increase rubber production needs industri.5) Cooperation with investors to build a processing plant karet.6) increasing cultivation technology of rubber. 7) Expanding plantations of rubber.8) Promoting the use of seedlings (clones) superior. Keywords: Agribusiness, Development, Rubber